Should we use proton pump inhibitors as an add-on treatment in hereditary hemochromatosis? - Kani, Haluk Tarık; Gündüz, Feyza (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Kani HT, Gündüz F. Should we use proton pump inhibitors as an add-on treatment in hereditary hemochromatosis? Turk J Gastroenterol 2018; 29: 254-5.